Are Manipulation Checks Necessary? - Hauser, David J.; Ellsworth, Phoebe C.; Gonzalez, Richard (Frontiers in Psychology, 2018)
Researchers are concerned about whether manipulations have the intended effects. Many journals and reviewers view manipulation checks favorably, and they are widely reported in prestigious journals. However, the prototypical manipulation check is a verbal (rather than behavioral) measure that always appears at the same point in the procedure (rather than its order being varied to assess order effects). Embedding such manipulation checks within an experiment comes with problems. While we conceptualize manipulation checks as measures, they can also act as interventions which initiate new processes that would otherwise not occur. The default assumption that manipulation checks do not affect experimental conclusions is unwarranted. They may amplify, undo, or interact with the effects of a manipulation. Further, the use of manipulation checks in mediational analyses does not rule out confounding variables, as any unmeasured variables that correlate with the manipulation check may still drive the relationship. Alternatives such as nonverbal and behavioral measures as manipulation checks and pilot testing are less problematic. Reviewers should view manipulation checks more critically, and authors should explore alternative methods to ensure the effectiveness of manipulations.